Peran Kiai dalam Pengembangan Pesantren: Studi Kasus Pondok Pesantren Manbaul Hikmah Kaliwungu Kendal Indonesia - Fanny Zakkiyah; Rasdi Ekosiswoyo; Achmad Rifai (Bulletin of Indonesian Islamic Studies, 2023)
This paper discusses the role of kiai in the decision-making process of pesantren development innovation and the impact of pesantren development innovation on learning activities in pesantren. This paper used qualitative research. Data were obtained through interviews and participatory observation. Data analysis was conducted using an interactive model including data collection, data reduction, data presentation and conclusion drawing. The findings of this study are the role of the main kiai or founder of the pesantren in the form of giving decisions on innovations implemented by Kiai Basyar Rohman. He is a figure who is considered to play a role as a carrier of change, an agent of reform, as well as an implementer of innovation in accordance with the qualifications and abilities he has from his previous experience managing pesantren. The success of pesantren innovations carried out was supported by all internal parties of the pesantren including santri and other ustaz. The impact of the development of pesantren education implemented by Kiai Basyar made Pesantren Manbaul Hikmah a combination pesantren (hybrid pesantren between modern and salaf) which did not eliminate the main characteristics of its salaf. In the morning, santri study in formal schools, and when they return to the pesantren, they carry out routine pesantren activities as usual, and at night they attend madrasah diniyah.